NEW MEDIA: ISLAM AGAINST GLOBAL PROPAGANDA (ANTITHES AGAINST ISLAMOPHOBIA IN SOUTHEAST ASIA) - Salman Alfarisi; Mailin Mailin (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2021)
Abstract Reporting of terrorist acts in Indonesia has always been a hot topic of discussion. When reporting on the action related to radical Islamic groups automatically appears a negative stigma against Islam. The negative stigma presents Islamophobia and becomes a topic of discussion on social media that affects social and political interpretations of society. All feel entitled to provide views, comments, feedback and attitudes and seek to influence each other. Some Islamic teachings or terminology are stigmatized as the cause of the birth of acts of terror. Among them, the debate over the terminology of "infidel", "jihad", "khilafah" which is essentially a terminology that is in the Qur'an and even part of Islamic teachings. The mass media also reported incidents of violence that were not related to radical Islamic groups in Indonesia. Even though the perpetrators are individuals or groups who are adherents of a religion or come from a certain race, it is still possible not to attach a negative stigma to the religion and race of the perpetrators. There is no stigma that terminology, teachings or culture are referred to as the cause of the birth of acts of violence as stigma against Islam. Indonesia is one of eleven countries in Southeast Asia. Unlike some other countries in Southeast Asia, Indonesia is a country with a majority Muslim population. Unlike Laos, Myanmar, Cambodia and Thailand, these countries are predominantly non-Muslim. The world is witnessing the unpeaceful attitude shown by the Thai government towards the Muslims of Pattani, Yala, Narathiwat and southern Songkhla. The world is also witnessing the plight of the Rohingya Muslim population in Myanmar. Although Cambodia to this day has provided good protection for the champ Muslim community, the Khmer Rouge's bad behavior towards them was heartbreaking. The conflict that has occurred has given rise to discriminatory attitudes and even genocide against Muslim minorities. Whatever the reason, this also cannot be separated from the negative stigma against Muslims in these countries with Muslim minorities. Keywords: New Media, Islam, Global Propaganda, Antithesis, Islamophobia